Psychological Factors Affecting Athletes' Motivation and Performance in Competitive Sports in Mexico - Antonio, Juan (International Journal of Physical Education, Recreation and Sports, 2023)
Purpose: The study sought to investigate the Psychological Factors Affecting Athletes' Motivation and Performance in Competitive Sports in Mexico Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library Findings: Psychological factors significantly impact athletes' motivation and performance in competitive sports. High self-efficacy and clear goal-setting practices are associated with improved motivation and performance, while athlete burnout, often resulting from stress and overtraining, negatively affects both. Autonomy and self-determination foster higher motivation and better performance, as do positive coach-athlete relationships. Managing pre-competition anxiety is crucial, as high anxiety levels can reduce motivation and performance. These findings underscore the importance of addressing these psychological factors to optimize athlete performance in the realm of competitive sports. Unique Contribution to Theory, Practice and Policy: The study recommends that the education should focus on building psychological skills, such as goal setting, visualization, and stress management, which can significantly impact motivation and performance. Coaches and sports psychologists should work closely with athletes to create personalized mental training plans. Sporting organizations should adopt policies that mandate the use of performance profiling and individualized psychological support for athletes at all levels.